The Impact of Climate Change on Cooling Energy Demand in Indonesia Based on Representative Concentration Pathways (RCP) Scenarios - Desak Putu Okta Veanti; Rista Hernandi Virgianto; I Gusti Ayu Putu Putri Astiduari (Science and Technology Indonesia, 2022)
Air conditioning system in a building is necessary to maintain air temperature at a certain comfort level, especially in tropical coun- tries such as Indonesia. Global warming was believed to accelerate the increase in energy consumption for air conditioning as a consequence of rising surface temperatures. This study aims to quantify the changes in energy consumption used for air condi- tioning systems based on Cooling Degree Days (CDD) that is calculated from the daily average temperature in Indonesia based on RCP4.5 and RCP8.5 scenarios. Projections for the future scenarios is compared with the energy consumptions in 2010. The results showed that energy consumptions increase up to 10 kWh/m2 year in 2030 for both scenarios. In 2050 RCP4.5 shows slightly higher Ew than RCP8.5 in some regions. However, in 2100, RCP8.5 shows significantly higher energy consumption for air conditioning sys- tem. The eastern part of Middle Kalimantan, South Kalimantan, Southern part of East Kalimantan, Northern East Java, Northern part of Lampung, South Sumatera, and Southern part of Papua shows the highest changes (51 to 68 kWh/m2 year)